Worldwide scientific efforts on nursing in the field of SARS-CoV-2: a cross-sectional survey analysis - Xiao, Yanping; Xiao, Lele; Zhu, Ruizhi; Liu, Xueyin (The Journal of Infection in Developing Countries, 2023)
Introduction: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has been a global public health issue. This study aimed to characterize global nursing research on SARS-CoV-2. Methodology: Nursing-related publications through December 31, 2022, were identified using Scopus. The number of studies, study types, countries, institutions, journals, authors, h-index, total confirmed cases, total deaths, and the highest-cited studies were investigated. Results: In total, 12,427 studies were identified. The number of studies increased rapidly, particularly between 2020 and 2021, with a 2.36–fold increase. The United States published the most studies (3,289, 26.47%), followed by the United Kingdom (1,059, 8.52%) and China (877, 7.06%). Scientific productivity significantly correlated with the total confirmed cases (r = 0.701, p = 0.024) and total deaths (r = 0.804, p = 0.005). The United States had the highest h-index (80), followed by China (59), and the United Kingdom (57). The University of Toronto published the most studies (181), followed by Harvard Medical School (165), and the University of São Paulo (107). Gravenstein S (23) was the most prolific author, followed by Mor V (22), and Rosa WE (19). The International Journal of Environmental Research and Public Health published the most papers (436), followed by PLOS ONE (219), and BMJ Open (185). Conclusions: Several countries, institutions, journals, and authors contributed greatly to SARS-CoV-2-related nursing studies. Countries with larger numbers of confirmed cases and deaths tended to publish more nursing studies. The United States, United Kingdom, and China had the highest quantity and quality of studies.